2013
DOI: 10.1080/10941665.2012.697648
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Relationship between Climate Change Awareness and Action: An Origin-Based Perspective

Abstract: While it is now widely accepted by scientists and governments that human activity contributes to climate change, there is a lack of understanding whether this realisation is now gaining greater attraction with the general public than it had 5 or 10 years ago. Additional gaps in knowledge relate to the link between awareness and action, which could be hypothesised to have become stronger in light of evidence being produced of some projected climate changes occurring already. This article examines climate change… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
(57 reference statements)
0
8
0
Order By: Relevance
“…However, it is not clear whether marketing their business as "climate friendly" and attempting to attract environmentally concerned tourists to their businesses will pay further dividends. Although the public believes that climate change is a serious problem, prior research has found that these concerns do not influence their travel behavior or demand for ecofriendly holiday destinations (Becken, 2007;Bergin-Seers & Mair, 2009;Eijgelaar et al, 2010;Gössling & Schumacher, 2010;McKercher et al, 2010;Tiller & Schott, 2013). However, the recent research by Cohen and Higham (2011) suggests an increasing number of travelers with a "carbon conscience" may demand these actions by operators in the future.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…However, it is not clear whether marketing their business as "climate friendly" and attempting to attract environmentally concerned tourists to their businesses will pay further dividends. Although the public believes that climate change is a serious problem, prior research has found that these concerns do not influence their travel behavior or demand for ecofriendly holiday destinations (Becken, 2007;Bergin-Seers & Mair, 2009;Eijgelaar et al, 2010;Gössling & Schumacher, 2010;McKercher et al, 2010;Tiller & Schott, 2013). However, the recent research by Cohen and Higham (2011) suggests an increasing number of travelers with a "carbon conscience" may demand these actions by operators in the future.…”
Section: Discussionmentioning
confidence: 90%
“…Cohen and Higham's (2011) interviews with 15 UK consumers found a range of attitudes, including some who were unaware of the impact of air travel on climate change, several who were aware but unwilling to change their travel behavior, and others who were aware and starting to travel with a "carbon conscience" (p. 331). Becken's (2004) research found that just over a half of tourists thought global climate change was an issue for tourism, while a recent study of New Zealand residents found that just over a half believed that tourism contributed to climate change (Tiller & Schott, 2013). However, only a small minority changed their travel behavior as a result.…”
Section: Carbon Mitigation Actions By the Tourism Industrymentioning
confidence: 99%
See 1 more Smart Citation
“…Destinations like the Great Barrier Reef (GBR) are especially problematic from a sustainability perspective as they (i) represent globally significant cultural heritage under severe threat from multiple sources including climate change [10]; and (ii) are complex governance domains: they present significant management challenges as they are protected areas of social-cultural significance from the local to the global level and often entail cross-sectoral governance. They also contain multiple stakeholders whose diverse characteristics, values and interests may result in a wide range of perceptions and attitudes towards climate change and impact management (see [11,12]). The GBR, for instance, is a World Heritage Area and visitor destination, as well as a protected marine park, and its extensive geographic range off the east coast of Australia intersects multiple state and local jurisdictions and impacts numerous coastal communities.…”
Section: Pressures and Challenges To Global Marine Resourcesmentioning
confidence: 99%
“…Both authors' relative comfort with flying (as seemingly unquestioned behaviour) and assessment of its moral legitimacy predominated in our ethical decision-making when flying represented the only possibility for face-to-face interactions with loved ones living far away. The moral dissonance, or awareness-action gap, for individuals has been an increasing phenomenon with growing awareness of the climate change impacts of flying (Lovelock, 2014), but the moral intersection of family relationship maintenance and carbon-based mobility has received only limited discussion (Tiller and Schott, 2013). Our narrative analysis indicates that proximity ethics is very much worth exploring as a framework through which people legitimise flying behaviour, as seen in the absence of any perception of real moral dilemma among either author in the context of flying for family connections, despite regretting the carbon impact.…”
Section: Moral Legitimacy Of Flying For Family Reasonsmentioning
confidence: 99%